1999
DOI: 10.1111/j.1574-6968.1999.tb13484.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of enteroaggregativeEscherichia coliisolates

Abstract: Forty enteraggregative Escherichia coli (EAggEC) previously characterized by their ability to adhere to HEp-2 cells or/and their hybridization with the 1-kb EAggEC DNA probe were investigated for the presence of adherence factors and heat-stable enterotoxin (EAST1)-encoding genes. Only 45% of the isolates harbored the EAST1-encoding genes as detected by polymerase chain reaction. None of them hybridized with an AAF/II-encoding gene specific DNA probe and 35% (14/40) were positive in a PCR assay using primers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 23 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…However, 7.9% of the isolates were positive for aggC. In France, Rich et al [22] detected the presence of the aggC sequence in 35% of the strains, which did not yield a positive result with speci¢c primers for aggA, suggesting that a slightly di¡erent adhesin was present in these strains. The aafA gene sequence was found in 7.9% of the EAEC isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 7.9% of the isolates were positive for aggC. In France, Rich et al [22] detected the presence of the aggC sequence in 35% of the strains, which did not yield a positive result with speci¢c primers for aggA, suggesting that a slightly di¡erent adhesin was present in these strains. The aafA gene sequence was found in 7.9% of the EAEC isolates.…”
Section: Discussionmentioning
confidence: 99%
“…These isolates were positive for at least one of the EAEC virulence sequences described in EAEC strain 042 [18]. The presence of aggC and aggR genes in some of these isolates suggests that they may harbour a ¢mbrial adhesin related to AAF/I [22] and that, in these isolates, CLA possibly represent a variation of the AA pattern. The CLA pattern was previously identi¢ed by Gomes et al [3] in E. coli strains that did not hybridise with DNA probes associated with di¡erent virulence markers of diarrhoeagenic E. coli; however, those strains were not tested for virulence sequences of EAEC strain 042.…”
Section: Discussionmentioning
confidence: 99%
“…The aafA sequence that encodes the AAF/II pilin was not found either among the strains studied, although AAF/II is the only individual EAEC marker so far epidemiologically associated with diarrhoea [13]. In fact, in two recent studies conducted with larger collections of EAEC strains in Brazil less than 8.0% of the strains carried the aafA sequence [16,30] and this sequence was not found either among EAEC strains isolated in France [28]. In contrast, in southwest Nigeria the aafA sequence was highly prevalent [13], suggesting that geographical aspects may be involved in the prevalence of this adhesin.…”
Section: Resultsmentioning
confidence: 97%
“…However, expression of a bundle structure in these strains was not observed despite the fact that they also carried sequence similarity with aggC and aggR, which encode the usher and the transcriptional activator of AAF/I, respectively [27,28]. Studying one EAEC strain (E. coli 457) that carries an aggA gene similar (but not identical) to the aggA gene of prototype strain 17-2, Rich et al [28] also observed lack of expression of ¢mbrial structures and suggested that the two adhesins might not present the same structural arrangement. On the other hand, in the present study, strain 2521-1 produced a bundle-like structure (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%